Determinação de parâmetros que influenciam nas propriedades mecânicas de material fresado estabilizado granulométrica e quimicamente para emprego em pavimentação - Silva, Marcos Rodrigues da (2018)
The materials originated from the recycling of asphalt paving can become an important constructive alternative in the road sector, besides contributing to the sustainability policy. Due to the preservation importance of the raw materials and the significant costs of paving works, it is feasible to analyze economical and sustainable techniques for the implementation or maintenance of highways. The Reclaimed Asphalt Pavement (RAP) technique finds application, for example, in the construction of bases or sub-bases for pavements. However, there are still no dosing and design methodologies of mixtures of Reclaimed Asphalt Pavement cemented based on rational criteria such as exists in the case of concrete, in which the water/cement ratio plays a fundamental role in obtaining the desired strength. In this sense, the research evaluated, through laboratory tests, the feasibility of the use of mixtures of RAP and stone powder, chemically stabilized with Portland cement CP V-ARI, for the base layers of pavement, correlating the index porosity/volumetric content of cement (/%) with parameters of stiffness and resistance of the mixtures. The RAP material comes from the BR-392, while the stone materials are of basaltic origin of the Serra Geral formation. For the granulometric stabilization the content of 70% RAP and 30% of stone powder was determined; also, mixtures of cement-aggregate stabilized with the same granulometric curve, made of natural stone materials that served as reference mixtures. Chemical stabilization was 4%, 5% and 6% by volume. With the results of the resistance tests unconfined compressive, splitting tensile, flexural strength and resilient modulus, all with 7 and 28 days of cure, correlations of the mechanical properties with the characteristics of the mixtures were made through the ratio /%. The results showed that both, resistance and modules increased linearly with addition amount of cement and exponentially with decreasing of the porosity. The /% ratio proved to be an excellent rational criterion for the evaluation of behavior and prediction of resistance and modulus for all the studied mixtures. The mixtures with RAP presented viscoelastic characteristics derived from the asphalt binder inheritance present in their composition. Finally, the satisfactory performance corroborates the possibility of covering the studies and use of these materials.